O papel da Extensão na Universidade: a formação do professor de línguas e suas práticas no Curso Pré-Vestibular da UNIOESTE/Foz - Pradella, Bruna Shirley Gobi (2020)
University extension, in addition to one of the pillars of the public university, along with teaching and research, it is a way of uniting the University and community through activities that bring the knowledge produced within the University to the community. In this research, we will think about extension from the perspective of initial teacher training, as a way to reconcile theory and practical, in addition to providing experiences and knowledge that make up the teacher education process. From studies and empirical knowledge on the theme, the following questions emerged, which guided this investigation: does the academic of Letters, who is willing to act as a monitor in the pre-entrance exam, have a training that allows him to develop, in the preparatory classes for the writing of the entrance exam, the theoretical criteria established by the examining board? Exists an equivalence between the initial formation of the language teacher and its actuation in the preparatory classes for the entrance exam? How does the initial teacher training take place within the extension activity? With the purpose to find the answers to this problematization, we trace, as general objective: to verify how does the initial language teacher training, in graduation and on the extension project, with the purpose of verifying if there is equivalence between their training and the practice of the monitors, in writing classes of the pre-university course of UNIOESTE/Foz. In order to achieve the proposed objective, we support the research on the theoretical assumptions of Applied Linguistics. It is, therefore, a research based on ethnography, action research, of the qualitative, interpretative type, in which I observed my classes, while monitoring the discipline of Writing. Data collection was carried out through observation, recording of classes and unstructured interviews. As a result of this study the theoretical equivalences between the initial teacher education in undergraduate classes, in the pre-university entrance exam writing classes and in the UNIOESTE entrance exam writing test were confirmed, as well as the relevance of university extension of this formation initial language teacher.